Meeting Report: GBIF hackathon-workshop on Darwin Core and sample data (22–24 May 2013). Issue 3 (November 2014) - Wieczorek, John; Bánki, Olaf; Blum, Stan; Deck, John; Döring, Markus; Dröge, Gabriele; Endresen, Dag; Goldstein, Philip; Leary, Patrick; Krishtalka, Leonard; Tuama, Éamonn; Robbins, Robert; et al.
Abstract The workshop-hackathon was convened by the Global Biodiversity Information Facility (GBIF) at its secretariat in Copenhagen over 22–24 May 2013 with additional support from several projects (RCN4GSC, EAGER, VertNet, BiSciCol, GGBN, and Micro B3). It assembled a team of experts to address the challenge of adapting the Darwin Core standard for a wide variety of sample data. Topics addressed in the workshop included 1) a review of outstanding issues in the Darwin Core standard, 2) issues relating to publishing of biodiversity data through Darwin Core Archives, 3) use of Darwin Core Archives for publishing sample and monitoring data, 4) the case for modifying the Darwin Core Text Guide specification to support many-to-many relations, and 5) the generalization of the Darwin Core Archive to a "Biodiversity Data Archive". A wide variety of use cases were assembled and discussed in order to inform further developments.